Valorization of paper mill lime sludge via application in building construction materials: A review. (30th June 2019) - Vashistha, Prabhat; Kumar, Vivek; Singh, S.K.; Dutt, Dharm; Tomar, Gaurav; Yadav, Pooja
Highlights: Lime sludge utilization in concrete, mortars, fired bricks, ceramics and cement. 10–30% cement replacement in concrete and mortars by lime sludge is optimum. 25–30% replacement of fine aggregates by lime sludge is optimum. Bricks and ceramic production with lime sludge conserves less energy. Lime sludge eco clinker synthesizes with less carbon footprint and temperature. Abstract: This review paper encompasses the inclusive approach of lime sludge valorization in construction materials. Research studies based on cement and aggregate replacement by lime sludge concludes that 10–30% lime sludge is gainfully utilized in sustainable concrete and mortar. Additional prospect for lime sludge application in construction material is the production of cement and ceramics. Significant use of lime sludge in combination with supplementary cementitious materials such as silica fume, nanosilica and fly ash is recommended for the production of cement components and ceramics. The recommendations are also suggested in accordance with the outcome of the study.